About modern technologies in the construction sector of the economy - V. F. Zhuravel; A. E. Zhuravel; A. V. Kharevich (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The construction industry is one of the leading in the Russian economy. Thanks to this industry, the state is developing, residential buildings are being built and infrastructure is developing. Digitalization of the construction industry is one of the main directions of the strategy for the development of the construction industry and housing and communal services, which is being implemented by the state. Digitalization of the construction industry means the use of digital technologies and tools to improve the design, construction and operation of buildings and structures.Goal – to study processes that are significantly influenced by blockchain technologies and robotization of business processes.Materials and methods. To solve the tasks set, general scientific methods of cognition were used: systemic and process approaches, expert methods. The theoretical and methodological basis was the works of domestic and foreign scientists on the topic of digital transformations in the investment and construction sector.Results and discussion. This article discusses the latest technologies in the construction industry, analyzes modern technologies and innovations that lead to large-scale digitization of the entire construction business of our country. The article describes the advantages of cloud services when creating a business project in construction. Some innovative products that implement in practice the concept of increasing productivity and optimal resource management in the construction industry are considered. The processes that are significantly influenced by blockchain technologies and the robotization of business processes are studied. It is concluded that it is expedient to develop and implement construction innovations in the modern economy in order to influence the efficiency of the construction business, its business processes, from engineering surveys to operation.Conclusion. The conclusion is made about the expediency of developing and implementing construction innovations in the modern economy in order to influence the efficiency of the construction business, its business processes, from surveys to operation.